Cervical aortic arch in the pediatric population: a meta-analysis of individual patient's data - Baudo, Massimo; Varrica, Alessandro; Reali, Matteo; Saracino, Antonio; Carminati, Mario; Frigiola, Alessandro; Giamberti, Alessandro; Lo Rito, Mauro (Frontiers in Cardiovascular Medicine, 2023)
Background This is the first meta-analysis to analyze all reports of published pediatric cases of cervical aortic arch (CAA) by highlighting the clinical characteristics and treatment outcomes using the reported individual data of the patients. The aim of the study is to investigate the clinical features and surgical outcomes of such a rare disease in the pediatric population. Methods A comprehensive search was conducted in various academic databases, including PubMed, ScienceDirect, SciELO, DOAJ, and Cochrane Library, until June 2022 for case reports describing the presence of cervical aortic arch in the pediatric age. Case reports and series were included if the following criteria were met: (1) description of the cervical aortic arch; (2) patient of pediatric age; and (3) published in the English language. All other types of publications that lacked patient-specific information were excluded from the analysis. This systematic review was conducted in accordance with the PRISMA guidelines. The primary outcome measure of the analysis was early and late mortality. Results The literature search identified 2,272 potentially eligible articles, 72 of which met our inclusion criteria with 96 patients including the author's institutional case. At a median of 365 (90–730) days, the overall cohort registered a 7.3% (7/96) mortality rate. In the subset of patients who underwent surgery, the mortality rate was also 7.3% (4/55), and the mortality rate following surgery to treat only CAA was 2.4% (1/42). Dyspnea was identified as an independent determinant of mortality by employing the univariable Firth bias-reduced logistic regression method. Conclusion Cervical aortic arch is a rare congenital heart disease that poses treatment challenges due to the high anatomical variability, diverse clinical presentations, and the presence of other concomitant diseases. The surgical treatment appears to be a safe and effective approach for resolving the symptoms, although it needs to be tailored individually for each patient. Systematic Review Registration https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=346826, Identifier: CRD42022346826.